Effectiveness of Media Intelligence in Supporting the 2024 Regional Elections - Siboro, Trevian (Proceedings of Police Academy, 2024)
The 2024 Regional Elections in Indonesia, held in conjunction with legislative and presidential elections, mark a critical moment for democratic governance, presenting both opportunities and complex challenges in maintaining security and order. The simultaneous elections introduce new risks in the form of misinformation, computational propaganda, and cyber threats due to advancements in information technology and the spread of the post-truth phenomenon. In response, the Indonesian National Police have implemented "Operation Mantap Praja 2024," an initiative designed to secure each stage of the electoral process. This study explores the strategic application of media intelligence within this operation, specifically in areas of early detection and information monitoring, to anticipate and address security vulnerabilities in real time. Media intelligence plays a pivotal role in this context by enabling the analysis of vast data from various media sources, utilizing open-source intelligence (OSINT), data mining, and machine learning techniques. This capability allows for timely intervention and proactive measures against potential threats, enhancing the resilience of public security efforts during the electoral period. Key areas of focus include digital leadership, resource allocation, and the integration of media intelligence with conventional policing strategies. Findings indicate that effective application of media intelligence not only strengthens public security but also supports the democratic process by mitigating polarization and the spread of misinformation. This research contributes valuable insights into how media intelligence can be institutionalized within law enforcement to safeguard democratic practices, particularly in an era characterized by rapid technological change and heightened political dynamics